MANAJEMEN STRATEGI PELAKSANAAN KURIKULUM DALAM MEWUJUDKAN MADRASAH UNGGUL (Studi atas MA Muhammadiyah Kota Metro) - Sujino Sujino (AT-TAJDID, 2017)
The public demand for quality or quality education is increasing. This phenomenon is at least influenced by two main factors namely; factors of globalization challenges and parents' awareness of the need for quality or quality education for their children. Another phenomenon that is not less interesting, today many schools are qualified and give more religious content became the first choice for parents, this condition is a challenge as well as opportunities for Senior High School  (MA) Muhammadiyah Metro City to rise from the shackles of dualism that is artificial and dualism management at once showcasing the various advantages that can be an attraction at the same time can invite public interest to make this institution as an option for the continuation of their children's education. This study aims to analyze management and strategy Implementation of the curriculum in realizing Senior High School (MA) Muhammadiyah Metro City Becomes a Superior School. This type of research is descriptive qualitative in which the data collection in this study was conducted by the method of observation, interview, and documentation study. Data that have been collected is then analyzed descriptively qualitative to then drawn conclusions. The results of this study will show that the management and implementation strategy of the curriculum in realizing Senior High School Muhammadiyah Metro City becomes a superior school. The results of this study recommend to management tiem in the implementation of the curriculum in realizing Senior High School Muhammadiyah Metro City Becomes a Superior School.